2019
DOI: 10.1016/j.resp.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of propofol on isolated neonatal rat carotid body glomus cell response to hypoxia and hypercapnia

Abstract: HighlightsThe intravenous anaesthetic propofol acts directly on carotid body glomus cells to inhibit their response to hypoxia.Propofol acts via novel mechanisms, as we excluded action via its known target receptors (nicotinic, GABA-ergic, or K+ channel).Inhibition of the hypoxic response is clinically relevant in anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 74 publications
3
13
0
Order By: Relevance
“…Our main result of a specific depression of HVR but not HCVR with partial neuromuscular blockade is consistent with previous work and as previously shown [8,9,[35][36][37][38]…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our main result of a specific depression of HVR but not HCVR with partial neuromuscular blockade is consistent with previous work and as previously shown [8,9,[35][36][37][38]…”
Section: Discussionsupporting
confidence: 93%
“…Our main result of a specific depression of HVR but not HCVR with partial neuromuscular blockade is consistent with previous work and as previously shown is most likely due to an inhibition of synaptic acetylcholine‐dependent nicotinic chemotransmission within the carotid body. This is interesting because such separation of effects on hypoxic and hypercapnic stimuli usually implies a drug effect directly on the carotid body type‐1 glomus cell.…”
Section: Discussionsupporting
confidence: 93%
“…Experiments by Reyes and colleagues showed that pharmacological cholinergic antagonism in cats does not eliminate hypoxia induced chemoreflex hyperventilation, nor chemosensory excitation [ 15 ]. Similar findings were found in in vitro rat experiments, showing that cholinergic antagonists inhibit nicotine induced, but not hypoxia induced increases in intracellular calcium in type 1 cells or afferent nerve action potentials [ 16 , 17 ]. Still, in a whole carotid body model, the nAChr antagonist vecuronium did depress afferent nerve discharge [ 18 ].…”
Section: The Role Of Cholinergic Chemotransmission In Chemotransdusupporting
confidence: 82%
“…Animal studies using an isolated carotid body‐nerve preparation have confirmed that non‐depolarising neuromuscular blockade inhibits this response to hypoxia . However, nicotinic antagonism does not inhibit the response of the isolated glomus cell to hypoxia and these results together indicate that the action of drugs like rocuronium is at the synapse, not directly on the glomus cell and, in turn, that ACh is a clinically‐relevant neurotransmitter at this junction .…”
Section: Depression Of Hypoxic Chemoreflexmentioning
confidence: 98%
“…. Propofol also depresses the isolated glomus cell hypoxic response but by a unique non‐TASK, non‐nicotinic, non‐GABA, non‐5‐HT mechanism . In other words, the combination of residual general anaesthetics directly depressing the glomus cell by various mechanisms and of NMBs depressing the synapse, is potentially synergistic in profoundly depressing the overall hypoxic response.…”
Section: Depression Of Hypoxic Chemoreflexmentioning
confidence: 99%